The Process Of Teaching Writing At The Second Semester Of English Department In Muhammadiyah University Of Surakarta In 2014/ 2015 Academic Year - Kurmaningrum, Sherly Dwi, Dra. Aryati Prasetyarini, M.Pd, Siti Fatimah, S. Pd, M. Hum (2015)
The objectives of the study are to describe the process of teaching writing at the second semester of English Department in Muhammadiyah University of Surakarta in 2014/ 2015 academic year and describe the problems faced by the teacher in teaching writing process. In this research,there are five components of teaching learning process that the writer analyze, such as: (1) Learning Objective. (2) The Syllabus. (3) The Material. (4) The Media. (5) The Technique and the problems faced by the teacher. This study is a descriptive qualitative research. The data are taken from observation, interview, and document. In collecting the data, the writer employs observation and interview. The technique for analyzing data is data reduction, data display, and conclusion and verification. The results of this study are: (1) Learning Objective of writing to make ths students able to develop paragraph and apply coherent and cohesion in making paragraph. (2) The type of syllabus is task based syllabus. (3) The material used is from the book or internet and focus on paragraph development. (4) The media used in teaching learning process is handout, which makes the students understand well. (5) The technique used in teaching writing process is controlled composition which can make the students not bored with the material and they are interested in the material. There are three problems faced by the teacher in teach writing class such as, the students vocabulary, the student's plagiarism, and the student's interest.